Tinjauan Hukum Islam terhadap Tindak Asusila yang Terjadi di Lingkungan Pondok Pesantren - Viennalia; Sarah; Aditha; Salwa (Albayan Journal of Islam and Muslim Societies, 2025)
This study aims to analyze sexual offenses, occurring within Islamic boarding schools from the perspective of Islamic law. This study employs a qualitative method with a normative legal approach through an analysis of verses from the Qur’an, hadith, legislation, and various works of Islamic criminal law literature related to the concepts of hudud, qishash, and ta’zir. The results of the study indicate that sexual offenses, within Islamic boarding schools can take various forms, such as sexual harassment, molestation, and sexual violence, influenced by the abuse of authority, weak oversight systems, and limited reporting channels for victims. From an Islamic legal perspective, sexual offenses, are prohibited because they contradict moral values and human dignity. The concept of hudud emphasizes the prohibition of all acts leading to adultery as an effort to preserve the purity and order of society. Meanwhile, the concept of qishash underscores the importance of justice and the protection of victims’ rights through the imposition of commensurate retribution on the perpetrator. The concept of ta’zir, on the other hand, grants the government the authority to determine sanctions in accordance with the severity of the offense and the needs of society. Thus, Islamic criminal law functions not only as an instrument for imposing sanctions but also as a means of prevention, victim protection, and moral guidance to create a boarding school environment that is safe and in accordance with the values of Islamic Sharia.